A randomized phase-I pharmacokinetic trial comparing the potential biosimilar tocilizumab (QX003S) with the reference product (Actemra®) in Chinese healthy subjects. (1st January 2021) - Zhang, Hong; Li, Xiaojiao; Liu, Jingrui; Li, Cuiyun; Wu, Min; Zhu, Xiaoxue; Sun, Jixuan; Fang, Min; Ding, Yanhua
Abstract: Purpose: QX003S is a biosimilar candidate for the reference tocilizumab, Actemra®. We investigated the tolerance, variability, and pharmacokinetics (PK) of QX003S biosimilar in healthy Chinese male subjects. Design: A randomised, double-blind, two-arm, parallel study was performed to examine the bioequivalence of QX003S (8 mg/kg) with that of Actemra® as a reference drug. Results: QX003S ( N  = 40) and Actemra® ( N  = 40) groups exhibited similar PK properties. The inter-subject variability ranged from 14.95% to 18.78%. The 90% confidence intervals of the ratios for Cmax, AUC0–t andAUC0–∞ in both groups were within the range of 80–125%. After administration, the number of subjects who tested positive for anti-drug antibodies (ADA) in the QX003S group and Actemra® groups was 6 (14.3%) and 14 (34.1%), respectively. Adverse reactions occurred in 100% and 97.6% subjects in the QX003S and Actemra® groups, respectively. The most common adverse reactions were decrease in fibrinogen level and neutrophil and leukocyte counts. Conclusion: The PK characteristics and immunogenicity exhibited by QX003S were similar to that of the reference product, Actemra®. The safety profile was similar in the two treatment groups with mild-moderate adverse effects. Trial Registration: The trial is registered at Chinese Clinical Trial website (http://www.chinadrugtrials.org.cn/index.html#CTR20190002 ) Key points: This was the first clinical report of a new proposed tocilizumab biosimilar, QX003S. This phase-I randomized, controlled study compared pharmacokinetics, variability, immunogenicity, and safety of QX003S vs. the approved tocilizumab product (Actemra@). The results demonstrate bioequivalence between BAT1806 and the reference products (Actemra@), as well as comparable immunogenicity, safety and tolerability profiles.